ANALISIS KESALAHAN BERBAHASA BIDANG SINTAKSIS PADA KARANGAN TEKS DESKRIPSI SISWA KELAS VII SMP NEGERI 1 SURAKARTA - Munashirah Munashirah; Zainal Arifin (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2025)
This research was conducted to describe Indonesian language errors in the field of syntax in descriptive text. This research aims to determine the types of syntactic errors, especially at the phrase and sentence level, which often occur in language use, both orally and in writing. This type of research is descriptive qualitative research. The research subjects were class VII E students of SMP Negeri 1 Surakarta, the subjects of this research were the parties who were the targets for data collection. The research object is a sentence that contains syntactic errors. The data collected is in the form of phrases and sentences in descriptive text. The data source in this research is written documents, namely descriptive text essays from class VII E students at SMP Negeri 1 Surakarta. Next, the data was validated using triangulation techniques and informant review through interactive analysis which consisted of four stages, namely data collection, data reduction, data presentation, and drawing conclusions or verification. The data collection techniques used in this research are observation and document study. Based on the research results that have been analyzed, the types of errors found include two errors, namely: (1) errors in the use of phrases. 21 (54%) errors include the use of non-standard words, ineffective phrase construction, and repetition of meaning which causes inaccuracies in delivery. information and (2) errors in sentence usage 18 (46%). These errors include the use of ineffective sentence structures, inappropriate use of conjunctions, repetition of meaning, and inappropriate use of punctuation.